Effect of pressure on the self-hole-doped superconductor RbGd2Fe4As4O2. (13th December 2018) - Sun, J P; Wang, Z-C; Liu, Z Y; Xu, S X; Eto, T; Sui, Y; Wang, B S; Uwatoko, Y; Cao, G-H; Cheng, J-G
Abstract: RbGd2 Fe4 As4 O2 is a newly discovered self-hole-doped stoichiometric superconductor, which has a hybrid structure with separated double FeAs layers and exhibits a high superconducting transition temperature T c   =  35 K. Here, we report the effect of pressure ( P ) on its T c and normal-state transport properties by measuring the temperature dependence of resistivity ρ ( T ) under various pressures up to 14 GPa with a cubic anvil cell apparatus. We found that the T c is suppressed monotonically to ca. 12.5 K upon increasing pressure to 14 GPa with a slope change of T c ( P ) at around 4 GPa. In addition, the low-temperature normal-state ρ ( T ), which is proportional to T n, also evolves gradually from a non-Fermi-liquid with n   =  1 at ambient pressure to a Fermi liquid with n   =  2 at P   ⩾  4 GPa. Accompanying with the non-Fermi-liquid to Fermi-liquid crossover, the quadratic temperature coefficient of resistivity, which reflects the effective mass of charge carriers, also experiences a significant reduction as commonly observed in the vicinity of a magnetic quantum critical point (QCP). Our results indicate that the stoichiometric RbGd2 Fe4 As4 O2 at ambient pressure might be located near a QCP such that the enhanced critical spin fluctuations lead to high- T c superconductivity. The application of pressure should broaden the electronic bandwidth and weaken the spin fluctuations, and then restore a Fermi-liquid ground state with lower T c .